Atas: registro de lutas discursivas da Escola Peixoto Gomide de Itapetininga - Melo, Rosineide de (2006)
This thesis presents the results o four study about reports of teachers' meetings at Escola Estadual Peixoto Gomide de Itapetininga, during 1917-1974. "Peixoto Gomide" was the second Normal School to be installed in São Paulo, becoming an importante reference in the qualification of teachers in our country. The core o four study concentrate on the discourses of teachers registered in the reports, that, is, in the discourses produced out the classrooms, in the interactions established among peers and superiors. We understand that the differential of this research to the academic community resides in the fact that we focus on the discourses that appeared in the activity of work of the teacher - Congregation, Counseling, Department, or School Cooperation Organ meetings - that is not the teaching practice in the classroom, which is always dealt with researchers of various areas. Se, that is the connection of this research with the area of "Language and Work" at LAEL, corresponding to the multiple natures of Applied Linguistics and the linking with other areas of sciences. To support the analysis, we developed studies about the architecture of the reports, reflections on the philosophical and sociological concepts of work, studies. on the circumstances of teacher's work in Brazil: legislation, organization of schools and organization of the profession. We built our theoretical-methodological support, mobilizing the notions of discourse, utterance, discourse genre, and discourse of the others from M. Bakhtin and his circle articulated with the discursive syntactics inspired in the study of. E. Benveniste, J. Cervoni, J.Authier-Revuz and R. Barthes. This theoretical-methodological set of concepts, connected with the History of Brazil, and, consequently, to the periods of diverse educational politics and to the immediate contexts, has permitted us to produce analysis turned to the dialogic perspective of the language. It was possible to see that: a) the report, discursively, is the registration of what can be written in and about one given enunciative situation, that is, It is the registration of what is permitted and not about what really happens in a meeting; b) the report contains a dialog whit the past (memory) and with the discursive future (registrations for posterity); c) the teacher discourse, reflected and refracted in the reports, presents as a resistance discourse, as a discourse of a political, ideological and social subject, responsible and respondable to this work